Structure – Functionality of lentil protein-polyphenol conjugates. (15th January 2022) - Parolia, Saakshi; Maley, Jason; Sammynaiken, Ramaswami; Green, Rick; Nickerson, Michael; Ghosh, Supratim
Highlights: Lentil protein isolate was conjugated with plant polyphenols. Equilibrium binding constants decreased in the order quercetin > ellagic acid > rutin. Random coil secondary structure of the proteins significantly increased upon conjugation. Conjugates were less surface active than the original lentil proteins. Radical scavenging and reducing power of the conjugates was better than the polyphenols. Abstract: Lentil protein isolate (LPI) was conjugated with plant polyphenols (quercetin, rutin, ellagic acid), and the structural and functional characteristics of the conjugates were determined in comparison with the proteins and pure polyphenols. The interaction between polyphenols and protein was achieved by a grafting method at pH 9.0 in the presence of atmospheric oxygen. Surface plasmon resonance measurements showed polyphenols' direct interaction with LPI, with the order of binding strength quercetin > ellagic acid > rutin. The degree of conjugation also followed the same order. Structural analysis of the conjugates was performed using FTIR, intrinsic fluorescence, and surface hydrophobicity. A significant improvement in DPPḢ radical scavenging and ferric reducing antioxidant power of the conjugates was observed compared to the polyphenols. However, there was a decrease in the surface activity of the conjugates compared to LPI. Such conjugation provides a novel way to combine the advantages of using plant protein and polyphenols in developing a novel food ingredient.